THE ANALYSIS OF INFLUENCE GEOMETRICAL PARAMETERS CHANGES OF RUNNING PART OF GAS TURBINE ENGINE ON DESCRIPTIONS OF THEIR INJECTIVITY - Панін, В. В.; Вознюк, А. П.; Шевченко, М. О. (Science-based technologies, 2009)
The paper deals with gas turbine engine flow channel geometrical parameters changes due to blades roughness and value of radial clearance in the compressor during the long operation. The proposed method of assessing the impact of these changes on engines transit modes.